Enjeux contextuels et écriture du genre du portrait dans la presse canadienne - Marc-François Bernier; Banafsheh Karamifar (Communication)
The authors examined journalism textbooks and found no mention of the critical role of context in choosing the appropriate form of writing. They looked into the question by comparing the writings in a selection of profile articles published by French-language media organizations in Canada. Using computer-assisted statistical and textual analysis, the authors will compare the writing designs of five textual levels, including the level of style. The results will be used to develop a teaching model.